Prevalence of Mediterranean FeVer Gene Mutations in Turkish Cypriot Population - Nilüfer GALİP and Ceyhun DALKAN and Ayşe TERALI and Nazan ÇOBANOĞLU and Ayfer ÜLGENALP and Nerin BAHÇECİLER and Salih KAVUKÇU (Archives of Rheumatology, 2017)
Objectives: This study aims to determine the carrier frequency and the most common mutations of the Mediterranean FeVer (MEFV) gene in healthy Cypriot population of Turkish origin. Patients and methods: A total of 296 healthy participants (102 males, 194 females; median age 30 years; range 1 to 81 years) were evaluated. The exon 2, 3, 5 and 10 of MEFV genes were amplified by polymerase chain reaction. Results: The participants demonstrated an extremely high carrier rate (12.5%). Most commonly detected mutations were E148Q and A74S, with rates of 7.3% and 2.8%, respectively. Conclusion: Mediterranean FeVer gene mutation types and carrier rates in Turkish Cypriot population are different than other Mediterranean populations in the region. MEFV mutation carriage is frequent in North Cyprus and familial Mediterranean fever might be one of the causes for end stage renal disease in Turkish Cypriots.